"Discurso y educación", de Rebollo Catalán, M. A. (2002):. Sevilla, Mergablum, 199 páginas - Pazos Caballo, Natalia (Revista Fuentes, 2016)
"DISCURSO Y EDUCACIÓN", de Rebollo Catalán, M. A. (2002):. Sevilla, Mergablum, 199 páginas